OFDI Determinants of Indian MNEs: Role of Indian Government as Influential Factor - Joseph Annadurai, Thanga Pandian (2011)
The recent boom in Indian economy can be explained through the intensity of inward FDI and outward FDI over the last two decade. Particularly, the increasing outward investment activity from Indian multinational firms is having a huge impact in the power balance of global economy and estimated growth of Indian economy. Hence it has become necessary to analyse the motives behind which these Indian MNEs are engaging in overseas investment. Although there is an extensive research work available to answer this question, literatures based on institutional analysis is very limited. Since the FDI activity for an emerging country like India is thoroughly controlled by the home government, it is essential to understand the significant role played by government in influencing OFDI decisions of EMNEs. So, this dissertation mainly identifies the major determinants of Indian MNEs’ decision to invest abroad and in particular the role of government as a crucial and influential factor. This research question is answered via empirical analysis using a sample size of 30 Indian MNEs who have invested across the globe between 1980 and 2010. The companies’ data such as sales, export and age, and host country’s GDP and physical distance are used to perform a regression analysis in order to find the correlation between various determinants (1990s economic reforms as one of the determinant) and test a set of hypothesis. The findings suggest the presence of a high correlation by export activity, experience and skills, and 1990s economic reforms with OFDI decisions of Indian MNEs. The rationale behind these findings are discussed and concluded with the suggestions for further research